La riduzione ad uso profano di una chiesa. Alcune applicazioni - Montini, G. Paolo (Quaderni di diritto ecclesiale, 2016)
The article assumes the knowledge of the conditions to reduce churches to profane use and it questions the destination to profane use in some peculiar situations, such as for example, the destination of an edifice of Cult of Churches or ecclesial communities that are not in full communion with the Catholic Church; a cemetery church; a church closed for worship. There emerges clearly that the reduction to profane use exists only with the cessation of the destination to divine cult of the sacred edifice